The effects of rice husk ash on growth, yield and lodging of flooded rice - Norafiqah Binti Suhaimi (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The purpose of this paper is to investigate the effect of silica rich rice husk ash and nitrogen rates on growth, yield and lodging of flooded rice. Huge amount of silica rich RHA are obtainable in numerous country of Asia as wastage cause a serious disposal complication. Reuse RHA could be a step to achieve agricultural sustainability. Lodging is one of major issues in rice production, severe lodging can lead to high yield loses. Si is considered as a beneficial element and nitrogen as an essential element for rice production. In order to study of effect of silicon and nitrogen on selected variety MRQ 76 (high yielding of Malaysian variety fragrant rice), a pot experiment conducted in the biosphere of the School of Bioprocess Engineering located in UniMAP, Perlis during September, 2016 till March, 2017. The experiment waslaid out in Completely Randomized Design (CRD) with three replications. There are 4 treatments with Si factor at three levels (0%, 10%, 20% and 30%) and nitrogen as another factor with two levels normal rate (120 kg N/ha) and double rate (240 kg N/ha). It showed that Si supply levels significantly better number ofpanicles, number of filled grains/panicle, 1000-grain weight and grain yields per pot. By increased nitrogen application with double rate presented that higher yield but reduce breaking resistance of plant. The maximum grain yield 6.676 ton/ha in 20% of RHA in normal rate N application and 20.011 ton/ha in 30% of RHA for double rate N application. The greater breaking resistance for normal rate was 1813.14 (g.cm) with lowest lodging index for normal rate N application. There are significant interactions between Si and N application where from the analysis resulted that NT3 (20% RHA/pot; normal rate N application) was the best level of RHA among the other treatments. Thus, for double rate N application DT3 (20% RHA/pot) is the best level of RHA for improving rice productivity.